2019
DOI: 10.1002/jlb.ma0119-021r
|View full text |Cite
|
Sign up to set email alerts
|

A skewed distribution and increased PD-1+Vβ+CD4+/CD8+ T cells in patients with acute myeloid leukemia

Abstract: The limited application of immunotherapy in acute myeloid leukemia (AML) may be due to poor understanding of the global T cell immune dysfunction in AML. In this study, we analyzed the distribution characteristics of 24 TCR Vβ subfamilies in CD3+, CD4+, and CD8+ T cells in AML patients and healthy controls. The percentage of TCR Vβ subfamily T cells was predominately lower in most AML cases, while it was increased in some cases. TCR Vβ2+T cells were increased in AML, particularly TCR Vβ2+CD4+T cells, which wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…With the recent development of targeted and immunotherapy, a number of ongoing studies aim to produce novel AML therapies, including conventional cytotoxic chemotherapies, genetic and epigenetic targeted therapies, and immunotherapies [3][4][5][6]. The T cell immune status of patients is an important factor related to the prognosis of leukemia [7][8][9][10][11]. Significantly, improvement in the clinical outcome of hematological malignancies was demonstrated by using immunotherapies such as CAR-T cell transfusion [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…With the recent development of targeted and immunotherapy, a number of ongoing studies aim to produce novel AML therapies, including conventional cytotoxic chemotherapies, genetic and epigenetic targeted therapies, and immunotherapies [3][4][5][6]. The T cell immune status of patients is an important factor related to the prognosis of leukemia [7][8][9][10][11]. Significantly, improvement in the clinical outcome of hematological malignancies was demonstrated by using immunotherapies such as CAR-T cell transfusion [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…To the Editor, Immune checkpoint (IC) blockade by inhibitors of the programmed cell death 1 (PD-1) and PD-1 ligand 1 (PD-L1) has significantly improved clinical outcome for a variety of solid tumors [1,2], while little is known about the role of ICs in leukemia [3]. Previous reports have shown that higher numbers of PD-1 + T cells are related to poor outcome for patients with acute myeloid leukemia (AML) [3]. Clinical trials using PD-1 inhibitors are ongoing to treat patients with a high risk for AML relapse [4].…”
mentioning
confidence: 99%
“…It is well known that M3 is a prognostically favorable subtype of AML. Previous studies have shown fewer defects in T cell proliferation and activation in M3 compared with other AML subtypes . Therefore, we tried to compare the distribution of Tim‐3 in T cells from different AML subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing data have shown that upregulation of immune inhibitory receptors also called as immune checkpoints, such as programmed cell death receptor‐1 (PD‐1), cytotoxic T lymphocyte‐associated molecule‐4 (CTLA‐4), T cell immunoglobulin mucin‐domain‐containing‐3 (Tim‐3), T cell lymphocyte activation gene‐3, and B and T lymphocyte attenuator, which can reduce T cell activation and promote T cell exhaustion, is the primary reason for cancer immunosuppression . Checkpoint inhibitor‐based immunotherapy, such as anti‐PD‐1, CTLA‐4, and programmed cell death ligand‐1 antibodies, has proved as novel and powerful therapy against solid tumors, such as lung cancer and improving overall survival .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation